Behavioral and synaptic circuit features in a zebrafish model of fragile X syndrome. - Ming-Chong Ng (Public Library of Science (PLoS), 2013)
Fragile X syndrome (FXS) is the most frequent inherited form of human mental retardation. It is characterized by cognitive impairment and physical and behavioral problems and is caused by the silencing of fmr1 transcription and the absence of the fmr1 protein (FMRP). Recently, animal models of FXS have greatly facilitated the investigation of the molecular and cellular mechanisms of this loss-of-function disorder. The present study was aimed to further characterize the role of FMRP in behavior and synaptic function by using fmr1 knockout zebrafish. In adult zebrafish, we found that fmr1 knockout produces the anxiolytic-like responses of increased exploratory behavior in light/dark and open-field tests and avoidance learning impairment. Furthermore, electrophysiological recordings from telencephalic slice preparations of knockout fish displayed markedly reduced long-term potentiation and enhanced long-term depression compared to wild-type fish; however, basal glutamatergic transmission and presynaptic function at the lateral (Dl) and medial (Dm) division of the dorsal telencephalon synapse remained normal. Taken together, our study not only evaluates the mechanism of FRMP but also suggests that zebrafish have valuable potential as a complementary vertebrate model in studying the molecular pathogenesis of human fragile X syndrome.